2013
DOI: 10.1111/risa.12085
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Hurricane Catastrophe Risk to Offshore Wind Power

Abstract: The U.S. Department of Energy has estimated that over 50 GW of offshore wind power will be required for the United States to generate 20% of its electricity from wind. Developers are actively planning offshore wind farms along the U.S. Atlantic and Gulf coasts and several leases have been signed for offshore sites. These planned projects are in areas that are sometimes struck by hurricanes. We present a method to estimate the catastrophe risk to offshore wind power using simulated hurricanes. Using this method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Other metrics, such as those relating to life-safety are not of primary importance for offshore wind as the turbine is normally unmanned, apart from brief periods to allow for maintenance activities [14]. Rose et al [15] quantified resilience of an OWT through robustness by estimating the cost incurred by loss of functionality after an extreme event. This allows the failure severity of different components to be compared within a unified metric, because each has a different material cost (replacement).…”
Section: Figurementioning
confidence: 99%
“…Other metrics, such as those relating to life-safety are not of primary importance for offshore wind as the turbine is normally unmanned, apart from brief periods to allow for maintenance activities [14]. Rose et al [15] quantified resilience of an OWT through robustness by estimating the cost incurred by loss of functionality after an extreme event. This allows the failure severity of different components to be compared within a unified metric, because each has a different material cost (replacement).…”
Section: Figurementioning
confidence: 99%
“…The risk factors present in the framework were chosen based on the known issues that cause damage to or affect the power generation of wind turbines. Hurricanes have the potential to cause significant damage to offshore wind turbines in many locations in the United States . Wind farms located in colder regions often have issues caused by icing on wind turbines.…”
Section: A Preliminary Risk Frameworkmentioning
confidence: 99%
“…Hurricanes have the potential to cause significant damage to offshore wind turbines in many locations in the United States. (14) Wind farms located in colder regions often have issues caused by icing on wind turbines. Ice storms and icing events during the winter months can result in decreased power generation and can also damage the turbines themselves.…”
Section: A Preliminary Risk Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…While these analyses showed the risk to individual wind plants, a larger concern for system operators is the number of turbines that might be simultaneously unavailable as a result of hurricanes. To evaluate this risk, Rose et al 56 developed a model to estimate the catastrophe risk to offshore wind power. This analysis showed that only a small fraction of offshore wind power in a region would be offl ine simultaneously because of tower buckling by hurricanes.…”
Section: Improved Siting Of Renewable Facilitiesmentioning
confidence: 99%